COLLECTIVE DIGITAL SIGNATURE PROTOCOLS ON ELLIPTIC AND HYPERELLIPTIC CURVES - Nelasaya, A. V.; Kozina, G. L.; Moldovyan, N. A. (Radio Electronics, Computer Science, Control, 2024)
New collective digital signature protocols on elliptic and hyperelliptic curves are proposed. Computational algorithms are illustrated with numerical examples.